2014
DOI: 10.1016/j.jagp.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Duration of Type 2 Diabetes with Cognitive Performance is Modulated by Long-Term Glycemic Control

Abstract: Objectives It is unclear why duration of type 2 diabetes (T2D) is associated with increased cognitive compromise. High hemoglobin A1c (HbA1c) has also been associated with dementia, and is the primary contributor to T2D complications. Here we investigated whether the association of duration of T2D with cognitive functioning is modulated by hemoglobin A1C levels. Methods This study examined non-demented community dwelling T2D elderly (n=897) participating in the Israel Diabetes and Cognitive Decline study, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 20 publications
(27 reference statements)
5
39
0
Order By: Relevance
“…Reports from previous studies have suggested that midlife rather than late life diabetes is a risk factor for dementia and that longer duration is associated with greater risk [28, 29]. Unfortunately our electronic medical record system, which was unable to capture midlife data for all participants in our cohort, did not allow us to address this issue.…”
Section: Discussionmentioning
confidence: 94%
“…Reports from previous studies have suggested that midlife rather than late life diabetes is a risk factor for dementia and that longer duration is associated with greater risk [28, 29]. Unfortunately our electronic medical record system, which was unable to capture midlife data for all participants in our cohort, did not allow us to address this issue.…”
Section: Discussionmentioning
confidence: 94%
“…As associations of the Hp genotype with cardiovascular disease have been consistently stronger in type 2 diabetes [50, 51], it would not be surprising if associations of Hp with cognition were also greater in the type 2 diabetes population. The use of follow up years in the registry as a surrogate for duration of type 2 diabetes was a truncated estimate for all those who already had diabetes when entering the registry, thus the reported values may reflect an under estimate [34]. Another limitation was the use of only one subtest from the WASI, Similarities, as a proxy for IQ.…”
Section: Discussionmentioning
confidence: 99%
“…Three sets of covariates were used for analyses: demographic characteristics (age, years of education and sex), type 2 diabetes-related characteristics (number of follow up years in the registry, a surrogate for duration of disease [34] and whether medication for type 2 diabetes was taken [no medication, hypoglycaemic medication, and insulin or insulin + hypoglycaemic medication]) and cardiovascular risk factors (BMI, creatinine, total cholesterol, triacylglycerols, and diastolic and systolic BP). The cardiovascular risk factors were calculated as the means of all assessments for each participant in the MHS diabetes registry.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, in the light of relationships of insulin [15], glycemic control [16], hypertension [12], and other diabetes-related characteristics with dementia risk in non-T2D individuals, discoveries from the IDCD study may not only be pertinent to T2D per se, but may generalize to all elderly. The overall hypotheses of the IDCD study are that glycemic control is a key factor and that not only it will be associated with cognitive decline, it will also modulate relationships of several other risk factors (such as the duration of disease [17] and inflammation [18]) with cognition, such that relationships will be stronger with poorer levels of glycemic control. Because T2D is associated with both neurodegenerative and vascular brain abnormalities [19], we hypothesize that both episodic memory (affected early in the course of AD) and executive functions and working memory (affected by cerebrovascular disease) will be associated with the risk factors.…”
Section: Introductionmentioning
confidence: 99%